Sosialisasi Pemanfaatan Jahe Merah Untuk Menurunkan Kadar Kolesterol Di Kelurahan Kaliwadas Kabupaten Cirebon - Fiki Setiawan; Ikhwani Ikhwani; Supriyatin Supriyatin; Hery Prambudi; Misika Alam; Een Agustina (BADAN PENERBIT STIEPARI PRESS, 2023)
Cholesterol sufferers in Indonesia are quite high, reaching 28% and 7.9% of people die from this disease. If treated too late, high cholesterol can endanger health and even lead to death. Decreased organ function in the elderly increases the risk of degenerative diseases. Pharmacological and non-pharmacological therapies are used to treat cholesterol. On the other hand, red ginger has been proven to be effective in lowering cholesterol levels. Red ginger contains flavonoid compounds with hypocholesterologenic effects and inhibits enzymes involved in cholesterol biosynthesis. The mechanism of action involves influence on enzyme activity, inflammatory and antioxidant properties. This study aims to determine the significant effect on cholesterol levels after consuming red ginger. The experimental research method was Purposive Sampling and the examination method used the fotometry. Data analysis used the SPSS program Paired T test with a sig value of 0.002 which was carried out on 19 elderly people aged 45-74 years with cholesterol levels >200 mg/dl by administering ginger. red 3.2 ml/kg BW every day for 14 days, in Kaliwadas Cirebon.. The results of the study showed that the results of checking cholesterol levels before treatment were found to be an average of 231 mg/dl and cholesterol levels after were found to be an average of 199 mg/dl. The conclusion of this research is that there is an effect of giving red ginger on total cholesterol levels with a percentage of 21.9%.